The concept of district health management in Malaysia - Z., Liyanatul Najwa; Z., Nadiatul Ima; Wan M. K., Noor Haslinda I.; S., Intan Syafinaz; H., Hasneezah; S., VC Anuratha; I., Hafeez; I., Faisal; A. M., Rosliza (Community Health Society Malaysia (CHSM), 2016)
Background: In Malaysia, public health services sector are administered by the Ministry of Health through its central headquarters to the state and district offices. The District Health Offices particularly manage and coordinate the delivery of an effective, efficient and affordable health services in the districts throughout Malaysia.